Can Polyphenols be used as Natural Preservatives in Fermented Sausages? - Aleksandra Nikolić (Sciendo, 2020)
This study was aimed at the investigation into the influence of polyphenols on fermented sausages produced with and without nitrite addition, during storage which lasted for 280 days. Three types of sausages were produced and formed the three experimental groups: C – the control – sausages of usual composition containing nitrites; N+P - sausages with nitrites and polyphenols; and P - nitrite-free sausages with added polyphenols. The proximate chemical composition of all groups was in the range with that of dry fermented sausages. P sausages contained 0.3 mg nitrites per kg, while C and N+P contained 54.8 mg/kg and 52.2 mg/kg, respectively. Polyphenol-enriched sausages had significantly lower peroxide and TBARS values than C sausages. In all sausages lactic acid bacteria counts reached 8.9-9.9 log cfu/g, but decreased during storage to 4.3-4.8 log cfu/g at the end of the storage period. Micrococcaceae counts remained stable: 3.5-3.9 log cfu/g. In P and N+P sausages a significantly lower number of Pseudomonadaceae was observed than in the control. The lightness of C and P sausages was similar (L=50.2 and L=49.5, respectively), while N+P sausages were darker (L=42.5). C and N+P sausages had similar redness (a*=14.5 and a*=13.2, respectively) and yellowness (b*=5.9 and b*=6.4, respectively), but the values which correspond to redness and yellowness were lower in P sausages (a*=8.0 and b*=4.6). Sensory characteristics of all products were found to be very similar. The flavour of polyphenol-enriched sausages was considered to be better. The most dominant polyphenol in sausages was kaempferol-3-O-glucoside followed by quercetin, luteolin-7-O-glucoside, catechin and syringic acid. Nitrite-free polyphenol-enriched sausages reached the same shelf life as conventional sausages containing nitrites did, which is a promising result implying that polyphenols might be used as natural preservatives and nitrite substitutes. Simultaneous use of nitrite and polyphenols is questionable due to their interactions which should be further studied.